ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI REPORTING DELAY : STUDI EMPIRIS PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Donabella, Alfa Angelina; Fuad, Fuad (Diponegoro Journal of Accounting, 2015)
Corporate managers tend to do reporting delay when there is bad news in the financial statements. On the other hand investors will delay investment decisions until they obtain information in the financial statements. Accordance with the signaling theory, described by Spence, stating that investors acknowledge the elements in the financial statements as a signal describing a variety of things in the company, moreover the reporting delay can be used as a signal by investors in the initial investment decision. Thus, this study aims to determine the factors that encourage the company doing the reporting delay by using empirical studies on banking companies listed in Indonesia Stock Exchange 2010-2013.This study used secondary data from the financial statements of 39 banking companies on the Indonesia Stock Exchange website during 2010-2013. The data were analyzed using multiple linear regression with audit delay, audit opinion and improvement of audit opinion as independent variables, as well as the audit committee as a moderating variable in relation to the audit delay and reporting delay.The results of this study are consistent with the existing literature, the audit opinion and improvement of audit opinion negatively affect the reporting delay. While the audit delay does not significantly affect the reporting delay, as well as the audit committee can not moderate the relationship between audit delay and the reporting delay.